Kunyit sebagai agen anti inflamasi - Nasser, Ghalib Abdul (Wellness And Healthy Magazine, 2020)
Herb plant is a famous plant and has been used since ancient times as tradisional medicine. Turmeric or curcuma is derived from the plant Curcuma longa L (Zingiberaceae). Curcumin is one of healthfull components of tumeric. Inflammation is an adaptive physiological response induced by infection and tissueinjuriesandhas complex product series by the immune system. Usually synthetic drugs are the first line of defense againt acute and chronic inflammation but has side effects which disturb gastrointestinal and cardiovascular organs. Some of reasearch has demonstrated the mechanism curcumin as an anti-inflammatory agent. Research shows curcumin is a highly pleiotropic molecule capable of interacting with numerous molecular targets involved in inflammation. Curcumin modulates the inflammatory response by down-regulating the activity of cyclooxygenase-2 (COX-2), lipoxygenase, and inducible nitric oxide synthase (iNOS) enzymes, inhibits the production of the inflammatory cytokines tumor necrosis factor-alpha (TNF-a), interleukin (IL) -1, -2, -6, -8, and -12, migration inhibitory protein, down-regulates mitogen-activated, and monocyte chemoattractant protein (MCP). However, curcumin has poor bioavailability. several strategies have been explored to improve curcumin’s bioavailability, with modulation of the delivery system.